Simultaneous Measurements of Temperature and Viscosity for Viscous Fluids Using an Ultrasonic Waveguide - Jinrui Huang; Frederic Cegla; Andy Wickenden; Mike Coomber (Sensors, 2021)
The characterisation and monitoring of viscous fluids have many important applications. This paper reports a refined ‘dipstick’ method for ultrasonic measurement of the properties of viscous fluids. The presented method is based on the comparison of measurements of the ultrasonic properties of a waveguide that is immersed in a viscous liquid with the properties when it is immersed in a reference liquid. We can simultaneously determine the temperature and viscosity of a fluid based on the changes in the velocity and attenuation of the elastic shear waves in the waveguide. Attenuation is mainly dependent on the viscosity of the fluid that the waveguide is immersed in and the speed of the wave mainly depends on the surrounding fluid temperature. However, there is a small interdependency since the mass of the entrained viscous liquid adds to the inertia of the system and slows down the wave. The presented measurements have unprecedented precision so that the change due to the added viscous fluid mass becomes important and we propose a method to model such a ‘viscous effect’ on the wave propagation velocity. Furthermore, an algorithm to correct the velocity measurements is presented. With the proposed correction algorithm, the experimental results for kinematic viscosity and temperature show excellent agreement with measurements from a highly precise in-lab viscometer and a commercial resistance temperature detector (RTD) respectively. The measurement repeatability of the presented method is better than 2.0% in viscosity and 0.5% in temperature in the range from 8 to 300 cSt viscosity and 40 to 90 °C temperature.